Aqueous Batteries: Rational Construction of Self‐Standing Sulfur‐Doped Fe2O3 Anodes with Promoted Energy Storage Capability for Wearable Aqueous Rechargeable NiCo‐Fe Batteries (Adv. Energy Mater. 33/2020). Issue 33 (1st September 2020) - Yang, Jiao; Zhang, Qichong; Wang, Zhixun; Wang, Zhe; Kang, Lixing; Qi, Miao; Chen, Mengxiao; Liu, Wei; Gong, Wenbin; Lu, Weibang; Shum, Perry Ping; Wei, Lei
Abstract : In article number 2001064 Qichong Zhang, Wenbin Gong, Perry Ping Shum, Lei Wei and co‐workers demonstrate a facile and cost‐effective method to achieve self‐standing S‐doped Fe2 O3 nanowire arrays as a high‐performance anode for aqueous batteries. Twisted‐fiber aqueous rechargeable NiCo‐Fe batteries are successfully assembled with high capacity and energy density, leading to the development of textile‐based energy storage.